Concentration of Na+-taurocholate-cotransporting polypeptide expressed after in vitro-transcribed mRNA transfection determines susceptibility of hepatoma cells for hepatitis B virus = Im Titel ist das Pluszeichen hochgestellt - Oswald, Andreas; Chakraborty, Anindita; Ni, Yi; Wettengel, Jochen M.; Urban, Stephan; Protzer, Ulrike (Scientific reports, 2021)
Infection of hepatocytes by hepatitis B virus (HBV) depends on surface expression of its receptor Na+-taurocholate-cotransporting polypeptide (NTCP), but sufficient NTCP expression is lacking in most cell lines. NTCP can be introduced by plasmid transfection or transduction by viral vectors to render cells permissive for HBV. However, transient transfection of hepatocyte-derived cell lines is inefficient, resulting in inhomogeneous protein expression and does not allow to adapt the level of NTCP expression. We therefore utilized in vitro transcribed mRNA to introduce NTCP into cells. Optimization using alternative cap structures and nucleotide modifications rendered mRNA transfection into different non-hepatic and hepatic cell lines very efficient. After transfection of mRNA, surface expression and functionality of NTCP was demonstrated by staining with an N-terminal HBV-preS peptide and bile acid uptake. Introduction of NTCP by mRNA transfection increased susceptibility of hepatoma cells to HBV in a dose-dependent manner. Transfection of NTCP mRNA into non-liver cells, in contrast, supported bile acid uptake but did still not render the cells permissive for HBV, demonstrating the requirement for additional host factors. Introduction of candidate host factors by mRNA transfection will allow for fast and convenient analysis of the viral life cycle using a transient, but reliable expression system.